Results of a 200 hours lifetime test of a 7 kW Hybrid–Power fuel cell system on electric forklifts. (1st January 2021) - Hsieh, Chuang-Yu; Pei, Pucheng; Bai, Qiang; Su, Ay; Weng, Fang-Bor; Lee, Chi-Yuan
Abstract: Five prototype fuel cell hybrid–drive electric forklifts were built, and laboratory tests were used to confirm that they could function in a real warehouse environment. The electric forklifts were delivered to Far Eastern Group's Taoyuan, Taiwan A–mart supermarket warehouse for 200 h of operational testing. Each vehicle's hybrid–drive system included a 2.7 kW proton exchange membrane fuel cell stack and two auxiliary power sources, each composed of a lithium battery and supercapacitors in parallel. The components of the drive system could supply 7 kW of power. The system's potential advantages are low cost and high working flexibility. To collect sufficient data and determine whether this fuel cell hybrid–drive electric forklifts design could function in an actual warehouse environment, an initial test period of 200 h was considered. The vehicles were operated from 8:00–22:00 with 4–5 h of peak operating time. Highlights: The forklifts are transformed from fuel to fuel cells as power. Fuel cells, lithium batteries and supercapacitors are used as active powers. This research can avoid the disadvantages of fuel cells. This paper has 200 h of test and provides detailed operation data. A simple hydrogen economy calculation is carried out.